2011
DOI: 10.1371/journal.pone.0025952
|View full text |Cite
|
Sign up to set email alerts
|

An Angiotensin I-Converting Enzyme Mutation (Y465D) Causes a Dramatic Increase in Blood ACE via Accelerated ACE Shedding

Abstract: BackgroundAngiotensin I-converting enzyme (ACE) metabolizes a range of peptidic substrates and plays a key role in blood pressure regulation and vascular remodeling. Thus, elevated ACE levels may be associated with an increased risk for different cardiovascular or respiratory diseases. Previously, a striking familial elevation in blood ACE was explained by mutations in the ACE juxtamembrane region that enhanced the cleavage-secretion process. Recently, we found a family whose affected members had a 6-fold incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 62 publications
1
50
0
Order By: Relevance
“…These studies allow the representation of mature human ACE, as shown in Fig. 1 (Danilov et al, 2011). The N-domain of the molecule begins with Leu1 and extends to Pro601 .…”
Section: E Structure Of Angiotensin-converting Enzymementioning
confidence: 99%
See 1 more Smart Citation
“…These studies allow the representation of mature human ACE, as shown in Fig. 1 (Danilov et al, 2011). The N-domain of the molecule begins with Leu1 and extends to Pro601 .…”
Section: E Structure Of Angiotensin-converting Enzymementioning
confidence: 99%
“…Model of human somatic ACE. This model is a three-dimensional reconstruction of the electron microscopic appearance of porcine somatic ACE (the net) combined with available human X-ray crystal structures (Chen et al, 2010;Danilov et al, 2011). It shows the ACE N-domain (Leu1-Pro601), linker region (Pro602-Asp612), C-domain (Leu613--Pro1193), stalk region (Gln1194-Arg1227), transmembrane segment (Val1228-Ser1248), and intracellular domain (Gln1249-Ser1277) Corradi et al, 2006).…”
Section: E Structure Of Angiotensin-converting Enzymementioning
confidence: 99%
“…The second vital question is whether the secreted ACE in serum could represent the amount of all ACE protein expressed from all tissues of the individual. Recently, a study provided an important evidence that the secreted ACE in human serum is very minor part of expressed ACE in comparison to membrane-bound ACE [47]. Besides, Fagyas and his colleagues [48,49] showed that most of the secreted ACE in body fluid are blocked by natural ACE inhibitors in serum (e.g., serum albumins).…”
Section: Pharmarcogenetic Mechanism Of Ace I/d Polymorphism Adverselymentioning
confidence: 99%
“…Collaboration of our group with the University of Chicago has revealed a third ACE mutation present in a family of individuals where the affected members suffer from intermittent nausea, vomiting, fatigue and depression. 13 Investigation revealed dramatically elevated levels of plasma ACE (approximately 10-fold higher than normal) associated with a mutation in the ACE ectodomain (Y465D). Expression of recombinant ACE with this mutation in mammalian cells confirmed that the Y465D mutation causes increased ACE shedding.…”
Section: Ace Mutations That Affect Ectodomain Shedding and Their Implmentioning
confidence: 99%
“…Expression of recombinant ACE with this mutation in mammalian cells confirmed that the Y465D mutation causes increased ACE shedding. 13 This is remarkable because the mutation is distant from the stalk cleavage site and probably causes a change in the relative orientation of the two domains, allowing better access of the sheddase.…”
Section: Ace Mutations That Affect Ectodomain Shedding and Their Implmentioning
confidence: 99%